Two Cases of the Vascular Territory of a Single-pedicled Deep Inferior Epigastric Perforator Flap with a Vertical Midline Abdominal Scar. Issue 3 (11th March 2020) - Morita, Daiki; Numajiri, Toshiaki; Nakamura, Hiroko; Yamochi, Ryo; Tsujiko, Shoko; Sowa, Yoshihiro; Moriguchi, Yoshio
Abstract : Supplemental Digital Content is available in the text. Abstract : Summary: : The deep inferior epigastric perforator (DIEP) flap is becoming the gold standard for breast reconstruction using autologous tissue. If there are scars in the abdomen from previous surgery, it is necessary to judge the indication for using this flap carefully. Particularly in cases with vertical midline scars, the blood flow supply to the zone II can be compromised. Even when patients have a median abdominal scar, it has been reported that the blood flow can extend beyond the scar and reach several centimeters to about half of zone II. We performed breast reconstruction using DIEP flaps for 2 patients with vertical midline scars in the lower abdomen. Indocyanine green angiography was conducted intraoperatively to confirm the vascular territory with a single pedicle before cutting off the flap. One patient showed fluorescence contrast on the contralateral side across the midline scar. However, the fluorescence contrast was absent across the midline scar in the other patient. Based on this result, we investigated the possible vascular territory of a single pedicled DIEP flap in patients with vertical midline abdominal scars. We suggest that successful blood supply to zone II of a single-pedicled DIEP flap in a patient with a vertical midline abdominal scar is related to the location of the perforator and the property of the tissue in the midline near the perforator. However, because it is difficult to predict the vascular territory of a single pedicle before surgery, intraoperative evaluation using such techniques such as indocyanine green fluorescence imaging is important.